Berth and quay-crane allocation problem considering fuel consumption and emissions from vessels - Hu, Qing-Mi; Hu, Zhi-Hua; Du, Yuquan (Computers & industrial engineering, 2014)
•Vessels’ fuel consumption and emissions are considered by optimizing sailing speed.•Effects of quay cranes on operating cost and fuel consumption are considered.•Vessels’ emissions when moored are quantified and formulated.•Cooperative strategies between ports and shipping companies are discussed. Resolving the berth and quay-crane allocation problem improves the efficiency of seaside operations by optimally allocating berthing spaces and quay cranes to vessels, typically by considering a vessel’s sailing speed and arrival time at a port as constant parameters, while ignoring the impact of arrival times on fuel consumption and emissions when sailing. This work applied a novel nonlinear multi-objective mixed-integer programming model that considered a vessel’s fuel consumption and emissions, and then transformed this model into a second-order mixed-integer cone programming model to solve the problem’s computational intractability. Furthermore, the impact of number of allocated quay cranes on port operational cost, and a vessel’s fuel consumption and emissions was analyzed. Additionally, a vessel’s emissions while moored are also calculated based on wait time. Experimental results demonstrate that the new berth and quay-crane allocation strategy with a vessel’s arrival time as a decision variable can significantly improve vessels’ fuel consumption and emissions, the air quality around ports and utilization of berths and quay cranes without reducing service quality.